Caracterização histopatológica e imunoistoquímica das lesões pulmonares inflamatórias em cães naturalmente infectados por Leishmania infantum. - Lima, Bruno Medolago. [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
São poucos os relatos na literatura sobre o mecanismo de resposta tecidual dos pulmões de cães com leishmaniose visceral canina (LVC). A avaliação histopatológica revelou pneumonia intersticial com infiltrado inflamatório linfohistioplasmocítico em 17/62 cães (27,41%) com LVC do grupo de animais infectados (G1). Nos pulmões com alterações inflamatórias (n=17) foi identificado, com a técnica de imunoistoquímica, predomínio de linfócitos TCD3+ e baixa quantidade de macrófagos RCA-1 e CD204 positivos, além de formas amastigotas no interstício alveolar em 2/17 cães (11,7%). A fibrose foi classificada como discreta e observada no interstício pulmonar de 1/17 cão (5,88%). Houve correlação positiva entre o escore de inflamação e quantidade de linfócitos TCD3+ (p=0,0001) e macrófagos RCA-1 (p=0,0225) e CD204 (p=0,0239) positivos imunomarcados, mas negativa quando estes foram correlacionados com o estadiamento clínico e a presença de formas amastigotas pulmonares (p=0,1141, p=0,4853 e p=0,3285, respectivamente). Os macrófagos de fenótipo M2 corresponderam, em média, a 63,39% do número total de macrófagos pulmonares imunomarcados, sendo este subtipo predominante. De acordo com os resultados, as alterações inflamatórias pulmonares em cães com LVC não são comuns e, quando ocorrem, independem do parasitismo no tecido e do estadiamento clínico dos animais. O predomínio de macrófagos de fenótipo M2 indica se tratar de uma resposta imunológica do tipo Th2, contribuindo, assim, com a progressão da doença no tecido pulmonar.

There are few reports in the literature on the mechanism of tissue response in the lungs of dogs with canine visceral leishmaniasis (CVL). Histopathological evaluation revealed interstitial pneumonia with lymphohistioplasmacytic inflammatory infiltrate in 17/62 dogs (27.41%) with CVL from the group of infected animals (G1). In the lungs with inflammatory changes (n=17), using the immunohistochemical technique, a predominance of TCD3+ lymphocytes and a low number of RCA-1 and CD204 positive macrophages were identified, in addition to amastigote forms in the alveolar interstitium in 2/17 dogs (11, 7%). Fibrosis was classified as mild and was observed in the lung interstitium of 1/17 dogs (5.88%). There was a positive correlation between the inflammation score and the number of immunostained positive TCD3+ lymphocytes (p=0.0001) and RCA-1 (p=0.0225) and CD204 (p=0.0239) macrophages, but negative when these were correlated with clinical staging and the presence of pulmonary amastigote forms (p=0.1141, p=0.4853 and p=0.3285, respectively). M2 phenotype macrophages corresponded, on average, to 63.39% of the total number of immunostained lung macrophages, with this subtype being predominant. According to the results, pulmonary inflammatory changes in dogs with CVL are not common and, when they occur, they are independent of parasitism in the tissue and the clinical staging of the animals. The predominance of M2 phenotype macrophages indicates that it is a Th2 type of immune response, thus contributing to the progression of the disease in the lung tissue.
Histopathological and immunohistochemical characterization of inflammatory lung lesions in dogs naturally infected with Leishmania infantum.
Keywords: inflamação; leishmaniose visceral canina; microscopia; pulmões; inflammation; canine visceral leishmaniasis; microscopy; lungs